The Mediating Role of the Care Factor in the Effect of Nomophobia on Nurses’ Job Satisfaction - Öner, Uğur; Aslan, Sinan; Ekingen, Erhan (Makara Journal of Health Research, 2026)
Background: This study aimed to examine the mediating role of the Care Factor in the relationship between nomophobia and job satisfaction among nurses. Methods: A descriptive, cross-sectional study was conducted with 1,083 nurses working in a province in Turkey between May and September 2024. Data were collected using a Descriptive Form, the Fırat Nomophobia Scale (FNS), the Care Factor Scale (CFS), and the Job Satisfaction Scale for Nurses (JSSN). All analyses were performed using SPSS 25, including descriptive statistics, Pearson correlation, and regression. Mediation was tested using PROCESS Macro version 4.0 (Model 4). Results: The CFS-CS and CFS-CM subdimensions moderately mediated the relationship between nomophobia and job satisfaction, with effect sizes of −0.063 and −0.096, respectively. The total effect in the parallel mediation model was −0.159. Nomophobia was negatively correlated with both job satisfaction and the care factor, whereas the care factor was positively correlated with job satisfaction. Conclusions: The Care Factor significantly mediates the impact of nomophobia on job satisfaction, underscoring its importance in addressing technology-related stress in nursing environments. Therefore, interventions aimed at promoting digital well-being in nursing practice are recommended to reduce nomophobia and improve job satisfaction.